Congenital right coronary artery aneurysm with fistula to right ventricle associated with isolated pulmonary valvular stenosis. Issue 5 (17th April 2020) - Jaswal, Vivek; Thingnam, Shyam K. S.; Kumar, Vikas; Uppal, Lipi; Toshkhani, Dheemta
Abstract: Congenital aneurysmal dilatation of coronary artery with coronary cameral fistula is rare in childhood. We report an even rarer association of congenital right coronary artery aneurysm and right coronary artery to right ventricle fistula with bicuspid pulmonary valve stenosis and an intact ventricular septum in a 3‐year‐old child.